2002
DOI: 10.1088/0963-0252/11/3/308
|View full text |Cite
|
Sign up to set email alerts
|

Quiescent and unstable regimes of a helicon plasma

Abstract: Known for their ability to produce high densities at low power, helicon discharges have found many uses. However, it has been discovered that the plasma density saturates, and even falls for light ion gases, as the magnetic field is increased. Detailed measurements of fluctuations in plasma density reveal the onset of a strong, low-frequency electrostatic instability. This onset correlates well with density saturation and is predicted from a linear theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The destabilization is mainly controlled by the magnetic field strength, supposedly by influencing the typical drift waves scale s . This is in agreement with other experimental observations by Light et al 16,19 and Tynan et al 20 Finite Larmor radius effects are believed to be responsible for this threshold behavior. 1,2,27 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The destabilization is mainly controlled by the magnetic field strength, supposedly by influencing the typical drift waves scale s . This is in agreement with other experimental observations by Light et al 16,19 and Tynan et al 20 Finite Larmor radius effects are believed to be responsible for this threshold behavior. 1,2,27 …”
Section: Discussionsupporting
confidence: 93%
“…17, 18 Light and co-workers observed a low-frequency electrostatic instability above a critical magnetic field that was made responsible for saturation or decrease of plasma density with increasing magnetic field. 16,19 This instability was identified as a hybrid of resistive drift waves and Kelvin-Helmholtz instability. Tynan and co-workers presented first observations of drift waves in the new CSDX helicon plasma device.…”
Section: Introductionmentioning
confidence: 99%
“…With hydrogen and helium, n peaks and then falls at higher field. Light et al 32 found that B crit coincides with the onset of an instability. In Fig.…”
Section: Anomalous Transport In Helicon Plasmasmentioning
confidence: 99%
“…17 Although there have been many publications on helicon discharges, there have been few on low-frequency oscillations and in particular the control of these instabilities. Light et al 18,19 observed a low-frequency electrostatic instability only above a critical magnetic field and identified it as a mixture of drift waves and Kelvin-Helmholtz instability. Degeling et al 20 observed relaxation oscillations in the kilohertz range that were associated with the various types of mode coupling in helicon discharges and were the result of plasma gas pumping.…”
Section: Introductionmentioning
confidence: 99%